Cross-border cooperation of Subcarpathian Voivodship - Barczewska-Dziobek, Agata (Review of European and Comparative Law, 2016)
EU integration has set challenges for the regions in the Eastern Poland, espe-cially in the field of economic development to minimalize internal differences on the one site, but also it needed to improve the new methods of cooperation between the public entities located in the border area on the field of public tasks . Podkarpackie Voivodship in Poland is the one of the regions in which you record-ed the lowest indexes of development . The tool to improve the situation is appro-priate development planning taking into account the potential of location and cross-border cooperation .The article presents the legal basis and real course of the cross-border coopera-tion in Podkarpackie Voivodship . Formal possibilities are the associations and oth-ers contractual forms permitted under national law . Regional authorities use all available instruments including the financial support from EU programs . Effec-tiveness of this activity is changed and is subject of various restriction . One of the most important changes, positive, is the assumption of the territorial allocation of founds dedicated to support areas located on the eastern border of EU in the perspective 2014-2020 and inclusion of cooperation in a number of development priorities set out in strategic documents .